High performance epoxy nanocomposites with enhanced thermal and mechanical properties by incorporating amine-terminated oligoimide-grafted graphene oxide. (June 2020) - Khan, Muhammad Inshad; Siddiqi, Humaira Masood; Park, Chan Ho; Han, Junghun; Park, Hyeonjung; Kim, Bumjoon; Hassan, Muhmood ul; Akhter, Toheed
In this work, thermal conductivity and mechanical strength of a commercial epoxy resin were improved by incorporating an amine-terminated oligoimide modified graphene oxide (ATO-GO). For this purpose, the surface of GO was modified with flexible/stable imide backbone and amine terminals. The ATO-GO was incorporated in epoxy proportion to prepare series of nanocomposites. The terminal amino group of ATO-GO also acted as curing moiety for epoxy resin leading to good interfacial compatibility and dispersion in the epoxy matrix resulting in improved properties. The epoxy resin was cured with hardener Aradur-22962 and ATO-GO separately and the results of curing behavior were compared with each other, which clearly showed the curing action of ATO-GO. In the prepared ATO-GO-epoxy nanocomposites, the filler enhanced the thermal conductivity, hardness and elastic modulus without decrease in thermal stability even at higher filler loading. In previous studies, it is reported that at higher GO, filler-loading properties like elastic modulus, hardness values, and glass transition temperature ( T g ) were decreased. An enhancement of 59.5% in thermal conductivity was achieved for 5 wt% loading of ATO-GO filler as compared to neat epoxy. Along with this, thermal analysis revealed that the nanocomposites with 5 wt% filler loading have high T g and thermal strength. Nanoindentation results revealed that elastic modulus and hardness values enhanced by 104% and 147%, respectively, for the same nanocomposites. The enhanced thermal conductivity and good elastic behavior of the ATO-GO-epoxy nanocomposites demonstrated that these can be used as high-performance materials in electronic packing and electronic devices.